Border deaths at sea under the right to life in the European Convention on Human Rights - Komp, Lisa-Marie (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"This book focuses on border deaths at sea. It unravels how the interplay of the law of the sea and rules on jurisdiction widen the opportunity for states to make and enforce rules outside their territory, and questions whether this is also accompanied with an obligation to respect the right to life under the European Convention on Human Rights (ECHR) when doing so. By embarking upon the challenge of analysing a cross-border phenomenon in which direct encounters between state agents and the victims are few through the lens of legal obligations, the book unearths avenues for arguing that the ECHR is applicable to border deaths on the high seas and showcases the Court's creativity in bridging the gap between the Convention and people in need of protection. Furthermore, it demonstrates that the ECHR is applicable to border deaths occurring within the territorial seas of states. It discusses the right to life, as well as the specific obligations of states in respect to border deaths at sea, and demonstrates that in many instances, EU policies fall short of the standards set under the right to life. This book will be of key interest to scholars, students and practitioners in migrant rights, international human rights law, public international law including, refugee and migration law, maritime law, and security studies"--
Introduction -- Do European immigration policies cause border deaths? -- The legal landscape of border deaths at sea -- Application of the ECHR to the extraterritorial effects of immigration policies -- The right to life and extraterritorial effects of immigration policies -- Conclusion.
OCLC-licensed vendor bibliographic record.
Keywords: Convention for the Protection of Human Rights and Fundamental Freedoms -- (1950 November 5); Refugees -- Legal status, laws, etc. -- Europe; Right to life -- Europe; Territorial waters -- Europe; Emigration and immigration law -- Europe; Assistance in emergencies -- Law and legislation -- Europe; Search and rescue operations -- Law and legislation -- Europe; LAW / International